An extended APOBEC3A mutation signature in cancer - Adam Langenbucher; Danae Bowen; Ramin Sakhtemani; Elodie Bournique; Jillian F. Wise; Lee Zou; Ashok S. Bhagwat; Rémi Buisson; Michael S. Lawrence (Nature Communications, 2021)
The APOBEC mutation signature contributes to a significant percentage of human cancers. Here the authors via biochemical and computational analyses shed light on how DNA primary sequence and secondary structure jointly influence A3A substrate optimality.